Conferências locais, distritais e municipais de saúde: Mudança de escala e formaç\~ao de um sistema participativo, representativo e deliberativo de políticas públicas - Cláudia Feres Faria; Isabella L. Lins; Evelyn R. Lob\~ao; Jo\~ao Antônio P. Cardoso; Viviane Petinelli (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The aim of this paper is to analyze to what extent the scale changing impacts the dynamics of participatory, deliberative and representative of the Health Conference held in Belo Horizonte. The hypothesis is this changing of level - from the local, to district and to municipal level - impact both (1) the rules, imposing a greater degree of formality to the internal dynamics of the conference, and (2) the interactions that occur within these spaces.
Keywords: Z18; 330; health conference in Belo Horizonte; integrated system; deliberation; participation; representation